Komposisi Famili Ikan di Ekosistem Lamun Perairan Pesisir Bahoi Kecamatan Likupang Barat Sulawesi Utara - Muh Fahruddin; Muhammad Haikal Abdurachman; Adi Suriyadin; Heri Murtawan; Anita Prihatini Ilyas; Muhammad Aidil Huda (Cenderawasih University, 2023)
The Bahoi coastal area has long been used for various economic activities, such as recreational locations or marine tourism. In addition, the Bahoi coastal community also carries out a lot of activities in the seagrass ecosystem, if these activities are carried out continuously it will have a negative impact on the sustainability of the seagrass ecosystem as a habitat for various types of aquatic biota such as fish. This study aims to determine the composition of fish species and the ecology of seagrass ecosystems in Bahoi coastal waters, West Likupang District, North Sulawesi. The results of the composition of fish species found in Bahoi waters consist of fish families and genera found in seagrass ecosystems consisting of 15 namely Siganidae, Plostosidae, Pomacentridae, Labridae, Clupeidae, Apogonidae, Carangidae, Lutjanidae, Nemipteridae, Balistidae, Athenomoridae, Achanturidae, Scaridae, Zanclidae, and Tetraodontidae. The highest fish species composition was shown by the Pomacentridae family, namely 57.2% and Siganidae 44.9%. The results of measuring the value of the community structure obtained show that seagrass ecosystems in coastal Bahoi waters have a fish community structure in a stable condition. The types of seagrass found varied, consisting of 6 species with mixed vegetation. The highest seagrass density and the cover was shown by the large seagrass species, namely Enhalus acoroides and Thalassia hemprichii. Overall, seagrass cover in Bahoi waters is classified as a very rich seagrass cover. Dominance index of fish species in Bahoi coastal waters is dominated by the families Pomacentridae and Siganidae.